Are antidepressants helpful for treating depression in patients with cancer?. Issue 10 (October 2017) - Defrees, Dean Nathan; Wauters, Michael; Henkle, Sarah; Martin, Susan A.
Abstract : EVIDENCE‐BASED ANSWER : The answer is unclear. The evidence is conflicting concerning the effect of antidepressant medication given for depression and depressive symptoms in patients with cancer (No SOR given).